Development and validation of the Chinese version non-nutritive sweetener FFQ with urinary biomarker in children and adolescents. Issue 8 (13th August 2022) - Chu, Ying-Yueh; Chen, Yue-Hwa; Hsieh, Rong-Hong; Hsia, Shih-Min; Wu, Hung-Tsung; Chen, Yang-Ching
Abstract : Abstract: Objective: The purpose of the current study was to develop a validated FFQ to evaluate the intake of non-nutritive sweeteners (NNS) in child and adolescent Asian populations. Design: Intensive and overall market research was performed to create the applicable NNS-FFQ with thirteen food categories and 305 items. Six intense sweeteners, including acesulfame potassium, aspartame, sucralose, glycyrrhizin, steviol glycosides and sorbitol, were investigated. The validity and reproducibility of the NNS-FFQ were evaluated. The validity was further assessed by examining the consistency of reported NNS intake compared with urinary biomarkers using Cohen's κ analysis. Settings: This work was considered to be relevant in Asian societies. Participants: One hundred and two children and adolescents recruited from several clinics were invited to participate in the current study. Results: High content validity indices and high content validity ratio levels were revealed for each sweetener and food category. Reproducibility among subjects was satisfactory. Significant moderate correlations between estimated steviol glycoside/sucralose consumption and sensitive urinary biomarker levels were demonstrated ( κ values were 0·59 and 0·45 for steviol glycosides and sucralose, respectively), indicating that the NNS-FFQ can be used to assess an individual's NNS intake. The dietary intense sweetener consumption pattern evaluated in this measurement was similar to those observed in other Asian countries but differed from those observed in Western populations with respect to types and amounts of NNS. Conclusions: This validated NNS-FFQ can be an applicable and useful tool to evaluate NNS intake in future epidemiological and clinical studies.